AI IN MARKETING: TRANSFORMATION OR REPLACEMENT OF HUMAN ROLES? - Iroda Akhmadova; Hikmatova Parvina; Aliboyeva Madina; Khatera Arman (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
The rise of artificial intelligence (AI) in marketing has transformed traditional practices, automating routine tasks, refining data analysis, and enabling targeted customer engagement. This paper explores whether AI will replace or complement human roles in marketing, given its current limitations in creativity, emotional intelligence, and strategic vision. Through a review of recent studies and industry insights, this research assesses AI’s impact on job roles, customer interactions, and marketing efficiency, concluding that AI is unlikely to fully replace human marketers but rather serves as an indispensable tool that enhances productivity while preserving the unique contributions of human insight and empathy.